2022
DOI: 10.3389/fmicb.2022.993914
|View full text |Cite
|
Sign up to set email alerts
|

Full-length transcriptome analysis of the bloom-forming dinoflagellate Akashiwo sanguinea by single-molecule real-time sequencing

Abstract: The dinoflagellate Akashiwo sanguinea is a harmful algal species and commonly observed in estuarine and coastal waters around the world. Harmful algal blooms (HABs) caused by this species lead to serious environmental impacts in the coastal waters of China since 1998 followed by huge economic losses. However, the full-length transcriptome information of A. sanguinea is still not fully explored, which hampers basic genetic and functional studies. Herein, single-molecule real-time (SMRT) sequencing technology wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…To obtain more detailed information about the target species transcriptome, the strategy of pooling samples from different treatments or tissues has been frequently performed with SMRT sequencing [ 25 , 28 ]. For instance, three different growth stages and several nutritional culture conditions of the dinoflagellate Akashiwo sanguinea were collected for SMRT sequencing library construction [ 25 ]. For H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain more detailed information about the target species transcriptome, the strategy of pooling samples from different treatments or tissues has been frequently performed with SMRT sequencing [ 25 , 28 ]. For instance, three different growth stages and several nutritional culture conditions of the dinoflagellate Akashiwo sanguinea were collected for SMRT sequencing library construction [ 25 ]. For H .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, third-generation sequencing (e.g., single-molecule real-time [SMRT]) technologies have been able to address the shortcoming of NGS. Single-molecule real-time sequencing can obtain full-length transcript sequences, without assembly, providing a better opportunity to explore whole-transcriptome profiling in non-model species [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies of transcriptome data identified: (a) differentially expressed genes in dinoflagellates relative to lifestyle (Bellantuono et al 2019), and to biotic and abiotic stresses (Moustafa et al 2010;Lowe et al 2011;Wang et al 2019;Kang et al 2021), (b) the transsplicing of spliced-leader sequences at the 5′-end of mature mRNAs (Zhang et al 2007), (c) diversity of transcript isoforms (Chen et al 2022a), and, more recently in combination with genome data, (d) protein-coding sequences (Shoguchi et al 2013;Lin et al 2015;Aranda et al 2016;Shoguchi et al 2018;Chen et al 2020;Stephens et al 2020;González-Pech et al 2021;Chen et al 2022b), and (e) the differential editing of mRNAs (Liew et al 2017;Dougan et al 2022b) and differential exon usage (Dougan et al 2022a) in distinct growth conditions. In most cases, these studies employed standard RNA-Seq approaches for eukaryotes to generate transcriptome data, whereby mRNAs with polyadenylated tails are retained, and focused on protein-coding genes.…”
Section: Introductionmentioning
confidence: 99%